Answer: Here is the explanation. also it it +3y not -3y
Step-by-step explanation:
x+y+4+2y+1=x+3y+5 because
2y+y=3y
so now you have x+3y+4+1
4+1=5
now you have: x+3y+5
if you do not understand, What i am trying to say is, you need to add all of the same things.
Answer:
A
Step-by-step explanation:
This explanation mostly depends on what you're learning right now. The first way would be to convert this matrix to a system of equations like this.
g + t + k = 90
g + 2t - k = 55
-g - t + 3k = 30
Then you solve using normal methods of substitution or elimination. It seems to me that elimination is the quickest method.
g + t + k = 90
-g - t + 3k = 30
____________
0 + 0 + 4k = 120
4k = 120
k = 30
No you can plug this into the first two equations
g + t + (30) = 90
g + t = 60
and
g + 2t - (30) = 55
g + 2t = 85
now use elimination again by multiplying the first equation by -1
g + 2t = 85
-g - t = -60
_________
0 + t = 25
t = 25
Now plug those both back into one of the equations. I'll just do the first one.
g + (25) + (30) = 90
g = 35
Therefore, we know that Ted spent the least amount of time on the computer.
The second method is using matrix reduction and getting the matrix in the row echelon form, therefore solving using the gauss jordan method. If you would like me to go through this instead, please leave a comment.
Answer:
A group of seven friends each received one-half of a pound ofcandy. How much candy did they receive total?✓
0.5 pounds x 7= 3.5 poundsStep-by-step explanation:
Answer:
A
Step-by-step explanation:
6ft plus 1 3/4 is 7 3/4
Sorry for minimum explanation but I hope it helped!
Answer:
Your answer: 87
Step-by-step explanation:
Since you are given what both variables are in the equation, this problem requires you to plug it in.
12(6)+3(5)= ?
You can either do this in a calculator, or do this one step at a time.
12(6)=72
3(5)=15
72+15=87